2002
DOI: 10.1152/ajpheart.00431.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular remodeling and diastolic myocardial dysfunction in rats submitted to protein-calorie malnutrition

Abstract: . Ventricular remodeling and diastolic myocardial dysfunction in rats submitted to protein-calorie malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
2
24
0
8
Order By: Relevance
“…This comes in agreement with Ocal et al (2001) who reported that the diastolic function indices were not significantly affected in malnourished patients. Fioretto et al (2002) also reported that there is a geometric alteration of the left ventricle with preserved ventricular compliance and distensibility despite increased passive myocardial stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…This comes in agreement with Ocal et al (2001) who reported that the diastolic function indices were not significantly affected in malnourished patients. Fioretto et al (2002) also reported that there is a geometric alteration of the left ventricle with preserved ventricular compliance and distensibility despite increased passive myocardial stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…In normotensive animals, morphological, ultrastructural, and functional myocardial changes were slight. [77][78][79][80][81][82] However, in the hypertrophied heart of hypertensive rats, structural changes were more severe and were combined with ventricular and myocardial systolic dysfunction. [83][84][85][86] Therefore, severe food restriction induces mild morphological and functional changes in normal hearts, which are exacerbated in hemodynamic overloaded hearts.…”
Section: Clinical Consequences Of Cachexiamentioning
confidence: 99%
“…Estudos têm demonstrado o efeito permanente do déficit de peso corpóreo promovido pela agressão nutricional quando aplicada durante a gestação e aleitamento 2,24,25 ou somente no período de aleitamento 26,27 . Essas adaptações do organismo à desnutrição podem ser metabólicas e endócrinas.…”
Section: I S C U S S ã Ounclassified